Institutionalized physical activity curriculum benefits of medical students in Colombia (2016)
Background: Health authorities internationally have recommended implementing physical activity and exercise for health training programs within the curriculum of medical schools. The purpose of this evaluation was to determine the changes in physical fitness and health (Fitnessgram criteria) of a sports medicine and physical activity course implemented for 3rd year students in a private medical school in Bogotá, Colombia. Methods: Intervention was targeted to 13 medical student cohorts. Cardiovascular endurance (20 m shuttle run test), speed (20 m sprint), strength (push-ups and curl-ups in 30 s), and flexibility (sit and reach) were evaluated at the beginning and end of the school semester. It was a 54 semester-hour intervention (3 h/week), with 37 h (69%) of directed group-based physical exercise. Results: Five hundred and twenty-four students were evaluated with an average age of 20 ± 1.4 years; 341 (65.1%) were women. In all the fitness tests for men and women, a significant increase was found. The prevalence of a healthy cardiorespiratory capacity went from 47.8% to 89.1% in women (P < 0.001) and from 54.6% to 83.1% in men (P < 0.001). Body mass index and weight increased in both sexes. Discussion: The results of the current study showed that a 54 h physical activity course within the medicine curriculum had a positive impact on health-related fitness indicators in Colombian medical students